The productive sector of flowers and ornamental plants of Brazil, in the period from 2008 to 2013: updates, balance sheets and prospects - Junqueira, Antonio Hélio; Peetz, Marcia da Silva (Ornamental Horticulture, 2014)
The Brazilian floriculture business is one of the most dynamic and promising segments of contemporary agribusiness, displaying indicators of significant growth, in terms of number of producers, cultivated area and Gross Value of Production (GVP). This article reviews and updates the national and macro-regional data from these indicators, from an extensive and exhaustive research of statistical data and analyzes generated from companies and public and private agencies connected with the industry. Thus provides a comparative overview between the years 2008 and 2013, pointing to some trend phenomena of productive sector organization in the country.